Inquiry-based Physics Learning Integrated with Mobile Apps, Multiple Intelligences, and Local Wisdom: A Bibliometric Analysis of Research Trends and Scientific Literacy Implications - Alhusni, Hanan Zaki; Prahani, Binar Kurnia; Sunarti, Titin; Madlazim, Madlazim; Kurtulus, Muhammed Akif (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This bibliometric study maps and evaluates the publication landscape on inquiry-based physics learning that intersects with mobile applications, multiple intelligences (MI), and local wisdom, with attention to implications for scientific literacy. Scopus records were retrieved using a TITLE-ABS-KEY search and processed following PRISMA 2020 and PRISMA-S. The screening window was restricted to 2020–2025, English-language, final-status documents, and journal articles or conference papers/proceedings. From 138,162 initially identified records, 362 remained after year and subject filtering; 305 met eligibility criteria, and 99 unique documents were included after DOI/title deduplication (full flow and exclusion reasons are reported in the PRISMA diagram and accompanying table). Performance analysis (annual output, sources, authors, countries, and subject areas) and science mapping (co-authorship, keyword co-occurrence, co-citation, and bibliographic coupling) were conducted using Bibliometrix/Biblioshiny and visualized in VOSviewer with association-strength normalization and full versus fractional counting sensitivity checks. Results show a publication peak in 2020, a decline across 2021–2023, and a rebound in 2024. Conference proceedings dominate the corpus (≈91%), with Journal of Physics: Conference Series contributing nearly two-thirds of documents. Indonesia is the leading contributor by affiliation and country; Physics and Astronomy accounts for ≈48–49% of subject assignments, followed by Engineering (≈14%) and Computer Science (≈12%). Keyword networks center on “students” and “education computing,” while MI and scientific literacy occur infrequently and local wisdom appears peripheral, indicating an early-stage, technology-driven field. Limitation: the Physics subject-area filter likely underrepresents education-journal studies where MI and literacy are more explicitly operationalized. Future work should prioritize journal-level designs, validated scientific-literacy measures, and transparent term normalization and counting schemes.